2019
DOI: 10.1002/admi.201900821
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Temperature‐Dependent Substrate Decomposition on Graphene for Separable GaN Growth

Abstract: voltage, high mobility, high luminous efficiency, long service life, and tunable bandgap energy by adjusting the aluminum and indium composition covering from ultraviolet to infrared. However, there are drawbacks for GaN. For example, growing GaN on a sapphire or silicon (111) substrate generates dislocation due to lattice mismatch between the GaN epitaxial layer and the substrate. In addition, the strong chemical bond at the interface makes it difficult to separate the epitaxial layer from the substrate, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 37 publications
0
41
0
Order By: Relevance
“…For the use of graphene substrate, because graphene does not form the covalent bonds with the overlayer NWs, the interfacial strain can be efficiently released through the small footprint (25). Furthermore, the high chemical inertness and thermal stability of graphene do not cause the contamination to the NWs even above 1000°C (26)(27)(28). Hence, graphene is one of the ideal substrate materials that can resolve the issues mentioned above for growing high-quality optoelectronic components.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the use of graphene substrate, because graphene does not form the covalent bonds with the overlayer NWs, the interfacial strain can be efficiently released through the small footprint (25). Furthermore, the high chemical inertness and thermal stability of graphene do not cause the contamination to the NWs even above 1000°C (26)(27)(28). Hence, graphene is one of the ideal substrate materials that can resolve the issues mentioned above for growing high-quality optoelectronic components.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is well known that the use of Al 2 O 3 wafer with a large in-plane lattice mismatch of 16.1% is quite beneficial because of its large scalable and well-compatible processing for the conventional GaN growth. Meanwhile, Park et al (28) have recently reported that the sapphire wafer is more stable than GaN substrate under harsh reaction conditions of hydrogen-and ammonia-rich high growth temperature of more than 1000°C when the surface is coated with graphene, and graphene is also robust in the same ambi-ence. Thus, it is expected that such tolerance of Al 2 O 3 is exploitable to allow recycling of the wafer after the release of the overlayer.…”
Section: Introductionmentioning
confidence: 99%
“…Damaged 2D materials and the associated defective van der Waals surfaces can lead to failure in releasing the membranes. For example, the graphene used for GaN growth can be damaged by H 2 carrier gas during growth at high growth temperature and by NH 3 or nitrogen plasma during metal organic chemical vapor deposition (MOCVD) or molecular beam epitaxy (MBE) growth. , Simultaneously achieving a high-quality epilayer and maintaining a robust van der Waals surface, which is the key to fabricating free-standing single-crystalline semiconductor membranes, has been one of the greatest challenges faced by the community.…”
mentioning
confidence: 99%
“…Meanwhile, the graphene fingerprint peaks were also detected on the GaN membrane. This indicates that the damage to the graphene layer occurs not only during the growth of GaN epilayer [ 9 , 37 ], but also due to the exfoliation. The graphene interlayer was probably ripped during the exfoliation, with some flakes of graphene stuck to the GaN membrane.…”
Section: Resultsmentioning
confidence: 99%